Pengembangan Buku Ajar Berbasis Model Pembelajaran ASSURE Untuk Mengajarkan Pemecahan Masalah - Anisatur Rohmah; Ria Wulandari (Natural Science, 2022)
Textbooks based on the ASSURE learning model can be an alternative learning resource that utilizes technology. This study aims to: 1) describe the validity of developing textbooks based on the ASSURE learning model to teach problem solving, 2) describe the practicality of developing textbooks based on the ASSURE learning model to teach problem solving, and 3) describe the effectiveness of developing textbooks based on the learning model to teach solution to problem. The research uses the ADDIE development model. The research data were obtained from validity sheets, learning implementation observation sheets, student activity observation sheets, solution sheets and constraints in learning, as well as problem solving descriptions. The results of data analysis show that the validity of the textbooks is 88.32 – 95.4% including valid qualifications, the practicality of textbooks is 78 – 100% declared reliable and the effectiveness of textbooks is 69% – 74% including the medium – high category. Thus, the development of textbooks based on the ASSURE learning model to teach problem solving is declared valid, practical and effective so that the product is feasible to use.